Mengembangkan Komik Digital sebagai Media Bimbingan: Sebuah Solusi Kreatif untuk Meningkatkan Efikasi Diri Siswa MTsN - Agus Qomaruzzaman; Abdullah Sinring; Farida Aryani (Technocouns: Journal of Technology in Guidance and Counseling, 2024)
This research develops digital comic media as a medium for guidance and counseling services to overcome student self-efficacy. The aim of this research is to find out: 1) An overview of the need for developing digital comic media to increase student self-efficacy in the learning process at MTsN 4 Bone. 2) Prototype of digital comic media in increasing student self-efficacy at MTsN 4 Bone. 3) The level of validity of digital comic media in increasing student self-efficacy at MTsN 4 Bone. 4) The level of practicality of digital comic media in increasing student self-efficacy at MTsN 4 Bone. This research uses a research and development model developed by Borg and Gall which was modified by the researcher. The instruments used in this research were interviews and questionnaires. The data analysis techniques used are quantitative data analysis and qualitative data analysis. The research results show that: 1) MTsN 4 Bone students have low self-efficacy so they need media that supports the guidance and counseling service process. 2) Prototype of digital comic media in increasing student self-efficacy at MTsN 4 Bone. 3) The level of validity of digital comic media in increasing students' self-efficacy shows very valid results. 4) The level of practicality of digital comic media in increasing students' self-efficacy shows very practical results.